THE USE OF LYRICSTRAINING.COM ON LISTENING CLASS OF FIRST SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM TEACHER TRAINING AND EDUCATION FACULTY (FKIP) UNIVERSITAS BANDAR LAMPUNG - Yanuarius Yanu Darmawan; Deasy Prischilla (Universitas Bandar Lampung, 2019)
The aim of this research is to investigate the students’ perceptions on the implementation of LyricsTraining.com in Listening class at first semester of English Education Study Program Teacher Training and Education Faculty (FKIP) Universitas Bandar Lampung. In this research, we used descriptive qualitative method. The purpose of this method was to investigate each phenomena or the students’ behavior then described it in paragraph. It was also used to get the detailed, precise, and well-organized explanation about their perceptions while using the LyricsTraining.com. The research was done for first semester of English Education Study Program Teacher Training and Education Faculty (FKIP) Universitas Bandar Lampung. To collect the data, I was observations, questionnaire, and interview. The collected data was analyzed by combining the result of observation, questionnaire, and interview in detail.The results of this research showed that LyricsTraining.com affected positively in increasing the students’ interest and motivation in learning listening.